Formation of lightweight materials of polyurethane - Muhammad Hashim, Nurul Nadiah (2018)
Lightweight materials, made up from either from natural and/or derived from the industrial process can be used to solve problems in construction for civil or even road as it is lower in density contrasting to the volume, but possess high strength in mechanical properties. The highlight in this study is the impact strength of rigid polyurethanes (RPUs) using different composition of water content in formulation and the relations to the pore size and density properties of the RPUs. The diphenylmethane 4,4-Diisocyanate (p-MDI) was reacted with formulated polyol with water as blowing agent in presence of catalyst and surfactant. The sample of the Polyurethane foam was made of formulated polyol of 1%, 2% and 3% of water content produced difference in viscosity of mixture affecting their cell morphology and mechanical strength of impact strength. Results focus on the possibility of the formulation of RPUs foam to reach adequate perfomance, in terms of low density with high excellent outcome allowing lightweight materials of RPUs to be used in future application for construction.